A pilot clinical trial of a near‐infrared laser vaccine adjuvant: safety, tolerability, and cutaneous immune cell trafficking. Issue 2 (7th September 2018) - Gelfand, Jeffrey A.; Nazarian, Rosalynn M.; Kashiwagi, Satoshi; Brauns, Timothy; Martin, Brent; Kimizuka, Yoshifumi; Korek, Skylar; Botvinick, Elliot; Elkins, Kristen; Thomas, Logan; Locascio, Joseph; Parry, Blair; et al.
ABSTRACT: Many vaccines require adjuvants to enhance immunogenicity, but there are few safe and effective intradermal (i.d.) adjuvants. Murine studies have validated the potency of laser illumination of skin as an adjuvant for i.d. vaccination with advantages over traditional adjuvants. We report a pilot clinical trial of low‐power, continuous‐wave, near‐infrared laser adjuvant treatment, representing the first human trial of the safety, tolerability, and cutaneous immune cell trafficking changes produced by the laser adjuvant. In this trial we demonstrated a maximum tolerable energy dose of 300 J/cm 2 to a spot on the lower back. The irradiated spot was biopsied 4 h later, as was a control spot. Paired biopsies were submitted for histomorphologic and immunohistochemical evaluation in a blinded fashion as well as quantitative PCR analysis for chemokines and cytokines. Similar to prior murine studies, highly significant reductions in CD1a + Langerhans cells in the dermis and CD11c + dermal dendritic cells were observed, corresponding to the increased migratory activity of these cells; changes in the epidermis were not significant. There was no evidence of skin damage. The laser adjuvant is a safe, well‐tolerated adjuvant for i.d. vaccination in humans and results in significant cutaneous immune cell trafficking.—Gelfand, J. A., Nazarian, R. M., Kashiwagi, S., Brauns, T., Martin, B., Kimizuka, Y., Korek, S., Botvinick, E., Elkins, K., Thomas, L., Locascio, J., Parry, B., Kelly, K.M., Poznansky, M.C. A pilot clinical trial of a near‐infrared laser vaccine adjuvant: safety, tolerability, and cutaneous immune cell trafficking. FASEB J. 33, 3074–3081 (2019). www.fasebj.org